2018
DOI: 10.7441/joc.2018.02.05
|View full text |Cite
|
Sign up to set email alerts
|

The Customer’s Brand Experience in the Light of Selected Performance Indicators in the Social Media Environment

Abstract: A brand is no longer what we tell the customer, it is what customers tell each other. The importance of using a social media mix for marketing purposes has never been greater than it is today. Ignoring these tools can have unfavourable effects on any company, whether in the form of lack of competitiveness or in the case of unnecessarily high costs for promotion with weak effect and targeting. We aim to examine the relationship between a customer's brand experience and loyalty to the brand, its image and willin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…The TPB model has an extra dimension of perceived behavioural control, which describes someone's belief and behaviour as well. Several research studies showed the significance and superiority of the TPB model over the TRA model (Ali et al, 2017;Shih & Fang, 2004;Prapavessis et al, 2015;Ercsey, 2017;Gavurova et al, 2018). According to Shih and Fang (2004), perceived behavioural control (PBC) is described as someone's conduct because of perceived comfort and strain through coordinated behaviour.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…The TPB model has an extra dimension of perceived behavioural control, which describes someone's belief and behaviour as well. Several research studies showed the significance and superiority of the TPB model over the TRA model (Ali et al, 2017;Shih & Fang, 2004;Prapavessis et al, 2015;Ercsey, 2017;Gavurova et al, 2018). According to Shih and Fang (2004), perceived behavioural control (PBC) is described as someone's conduct because of perceived comfort and strain through coordinated behaviour.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…The Swani and Milne research (2017) analyzed Fortune 500's content strategy focusing on services and goods. The findings from the multivariate multilevel Poisson model have shown that the use of corporate branding is more beneficial in the content on social media related services, while in case of selling goods it is more efficient to use the brand name in the content on social media (Gavurova et al, 2018). According to the Brookes study (2010), photos have an average of 22% more engagement than videos and 54% more engagement than text posts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumer behaviour analysis is a key aspect for the success of e-business. However, consumer behaviour towards changes in the Internet market changes as users gain experience Yu et al, 2005;Gavurova et al, 2018). Perceptions that affect their electronic purchase can have different impacts on consumer choice or buyback, because the use of information technology (IT) can change based on perceptions and attitudes .…”
Section: Literature Reviewmentioning
confidence: 99%